2015
DOI: 10.1016/j.bmc.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of N-aryl-6-methoxy-1,2,3,4-tetrahydroquinolines as tubulin polymerization inhibitors

Abstract: Thirteen new N-aryl 1,2,3,4-tetrahydroquinoline compounds (4a–f, 6a–c, and 8a–d) were synthesized and evaluated for antitumor activity and drug-like properties. Compound 4a exhibited high inhibitory potency with low nanomolar GI50 values of 16–20 nM in cellular assays, including excellent activity against the P-glycoprotein overexpressing cell line KBvin. Compound 4a inhibited colchicine binding to tubulin and tubulin assembly with an IC50 value of 0.85 μM, superior to the reference compound CA4 (1.2 μM) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…After several attempts, the quinazoline ring system was found to be a better structural core moiety, leading to a series of 2-substituted 4-phenylamino-quinazoline compounds 2 (Figure 2) with extremely high antitumor potency (GI 50 < 10 nM) in several cellular assays as well as in vivo. 15,16,17 However, the series 2 compounds did not show inhibitory activity in Mer TK assays (IC 50 >30 µM); thus, their antitumor target is not the Mer TK. However, when the phenylamino moiety (B-ring) was positioned at the 2-position of the quinazoline ring (A ring), the resulting 2-phenylaminoquinazoline compounds exhibited obvious inhibitory potency against Mer TK with low micromolar IC 50 values.…”
Section: Introductionmentioning
confidence: 96%
“…After several attempts, the quinazoline ring system was found to be a better structural core moiety, leading to a series of 2-substituted 4-phenylamino-quinazoline compounds 2 (Figure 2) with extremely high antitumor potency (GI 50 < 10 nM) in several cellular assays as well as in vivo. 15,16,17 However, the series 2 compounds did not show inhibitory activity in Mer TK assays (IC 50 >30 µM); thus, their antitumor target is not the Mer TK. However, when the phenylamino moiety (B-ring) was positioned at the 2-position of the quinazoline ring (A ring), the resulting 2-phenylaminoquinazoline compounds exhibited obvious inhibitory potency against Mer TK with low micromolar IC 50 values.…”
Section: Introductionmentioning
confidence: 96%
“…Our prior modeling studies further demonstrated that both 1a and 2 could dock within the tubulin−colchicine binding site and superimposed well with DAMA-colchicine (the bound ligand in the tubulin crystal structure, PDB code 1SA0). 12,13 In addition, the docking study showed that the 2-substituent on the quinazoline ring in series- 1 analogues overlapped well with the 7-side chain in DAMA-colchicine (Figure 1), thus indicating that the quinazoline 2-position has sufficient chemical space for structural modification. Consequently, in our current study, a series of new 4-(2-substituted quinazolin-4-yl)-3,4-dihydroquinoxalin-2(1 H )-one derivatives ( 6a−6t ) were designed by maintaining the new scaffold in 2 and introducing various substituents on the quinazoline ring 2-position.…”
Section: Introductionmentioning
confidence: 95%
“…Based on these results, the new scaffold in 2 was confirmed to be important for enhanced antitumor activity. Apart from the scaffold hopping, our prior structure optimizations on lead 1a 12 also revealed that the 2-substituent on the quinazoline ring was modifiable to improve druglike properties without loss of antitumor potency, especially with the introduction of an alkylamino side chain. Our prior modeling studies further demonstrated that both 1a and 2 could dock within the tubulin−colchicine binding site and superimposed well with DAMA-colchicine (the bound ligand in the tubulin crystal structure, PDB code 1SA0).…”
Section: Introductionmentioning
confidence: 99%
“…[119,120] Further substitution of the quinazoline by different quinolines, isoquinolines or purines do not improve the activity profile but the physicochemical properties can be substantially improved upon by the chemical modification of the quinazoline 2 substituent (42). [121] In a related approach of substitution of the phenyl rings of known CSL by pyridine analogues (Fig. 15) and based on the model microtubule destabilizer chalcone MDL-27048 (47) [122] natural products (as for example 46) were selected from a pharmacophore search [123] or synthesized as cyclopropylcarboxamide analogues, (48) [124] but in both instances only weak potencies were observed.…”
Section: Replacement Of the Phenyl Rings By Azinesmentioning
confidence: 99%